Art of the gold rush - Driesbach, Janice Tolhurst (University of California Press, 1998)
The California Gold Rush captured the get-rich dreams of people around the world more completely than almost any event in American history. This catalog, published in celebration of the sesquicentennial of the 1848 discovery of gold at Sutter's Mill, shows the vitality of the arts in the Golden State during the latter nineteenth century and documents the dramatic impact of the Gold Rush on the American imagination. Among the throngs of gold-seekers in California were artists, many self-taught, others formally trained, and their arrival produced an outpouring of artistic works.